(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The article highlights the importance and methodological aspects of the international project PIRLS "Research on the Quality of Reading and Text Comprehension". This study compares the level and quality of reading and text comprehension among elementary school students around the world, as well as its relevance to national education systems.